STRATEGI KEPALA SEKOLAH DALAM MENDORONG PROSES BELAJAR MENGAJAR INKLUSIF : ANALISIS KERJASAMA EFEKTIF DAN DAMPAKNYA - Victorynie, Irnie; Pasaribu, Muhammad Syafarudin; Nujud, Yasub Atsyir; Rafa, Juana (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to provide a description of several problems that occur in schools which become a description of the strategies carried out by a school principal in implementing inclusive teaching and learning activities in schools. Specifically, this research aims to determine (a.) The role of the principal in creating an inclusive culture in the school that supports all human resources in the school. (b.) Several things and strategies that must be done by a school principal in managing a conflict, and also knowing what characteristics a school principal must have in order to achieve these goals. The research method used by the author in this research uses a descriptive qualitative research method with data collection techniques using literature studies sourced from interviews, books, journals, documents and also valid websites. The results of this research show that in order to become a school principal who is able to implement inclusive teaching and learning activities in a school, you must have several strategies that can be implemented jointly by both teachers and students.